External debt and Economic Growth: the Nigeria Experience (2016)
This research work was aimed at ascertaining the impact of external debt on economic growth in Nigeria. Ex-post facto research design was adopted for the study. While data on Gross Domestic Product (GDP), External Debt Stock and External Debt Service Payment were obtained from World Bank International Debt Statistics, Exchange Rate data were collected from Central Bank of Nigeria Statistical Bulletin, 2013. The period of study was 1980-2013. Model was formulated and data were analyzed using Ordinary Least Square. Diagnostic tests were conducted using Augmented Dick Fuller Unit Root Test, Co-integration and Error Correction Model. The independent variable was GDP, while the explanatory variables were External Debt Stock, External Debt Service Payment and Exchange Rate. We discovered that External Debt had a positive relationship with Gross Domestic Product at short run, but a negative relationship at long run. Also, while External Debt Service Payment had negative relationship with Gross Domestic Product, Exchange Rate had a positive relationship with it. The paper concluded that exchange rate fluctuation had positive impact on the Nigerian economy while external debt stock and debt service payment had negative impact on the same economy. The study recommended amongst others, that Debt Management Office should set mechanism in motion to ensure that loans were utilized for purposes for which they were acquired as well as set a ceiling for borrowing for states and federal governments based on well-defined criteria.